Female Figures of the Jazz Age in Dorothy Parker’s Short Stories - López Cirugeda, Isabel (The Grove - Working Papers on English Studies, 2016)
Most criticism on Dorothy Parker (1893–1967) highlights her literary persona only to the detriment of the study of a profuse work comprising six decades of narrative, poetry and drama. Probably her best-known contribution to literature was her condition of the voice of the Jazz Age generation, shifting from acquiescence to irony. A corpus of Parker’s short stories written in the 1920s and early 1930s will be analyzed from feminist perspectives, such as those by Pettit, Melzer or Showalter, in terms of ‘appearance’, ‘social life’ and ‘bonds with men’ to determine whether her heroines respond to the stereotype of the flapper in the Roaring Twenties. Results show a satirized viewpoint conveying dissatisfaction regarding body, idleness and romance predicting many of the conflicts of women in the second half of the XXth Century.Key words: Dorothy Parker, short stories, flappers, Jazz Age, feminist criticism, body, satire. EL PERSONAJE FEMENINO DE LA JAZZ AGE EN LOS RELATOS DE DOROTHY PARKER ResumenLa mayor parte de los estudios sobre Dorothy Parker (1893–1967) se centran en su condición de personalidad del panorama escénico en detrimento de su profusa obra, con más de seis decenios de narrativa, poesía y teatro. Probablemente su contribución más reconocida sea haber dado voz a la generación de la Era del Jazz, con una visión que oscila entre la complicidad y la ironía. Las heroínas del corpus de relatos escritos por Parker en los años veinte y treinta serán analizadas bajo perspectivas feministas (Pettit, Melzer, Showalter) en términos de ‘apariencia’, ‘vida social’ y ‘relación con los hombres’ para determinar si se acomodan al estereotipo de la flapper. Los resultados muestran una sátira del modelo insatisfecho con su cuerpo y la vacuidad de su vida y amoríos que anuncia conflictos femeninos de la segunda mitad del siglo XX.Palabras clave: Dorothy Parker, relatos, flappers, Era del Jazz, crítica feminista, cuerpo, sátira.